Kritik Levinas terhadap Kebijakan Luar Negeri Realisme : Konsep Etika dan Tanggung Jawab terhadap “Liyan”: Levinas's Critique of Realist Foreign Policy: The Concept of Ethics and Responsibility to the “Liyan” - Merici, Angela (Jurnal Filsafat Indonesia, 2025)
This article aims to analyze the realist foreign policy in the international relation field from the perspective of ethics of the responsibility for “the Others” by Emmanuel Levinas. The methodology used is the qualitative method with the literature studies by collecting and analyzing the cases from the journal and media reports. The findings in this analysis is that realist foreign policy is in really opposite way to the concept of responsibility towards the "Other," where basic human rights are neglected and the domination of power by taking the benefits from the weak society either from the aspect of power, capability or even military from the example of anti-migrant policy by Hungary and Invasion of Irak by the United States in 2003. By the critique from Levinas, the state actors as the foreign policy makers in the states could put the impact of the policy for “the Others” in their consideration. This perspective of Levinas could also contribute to the alternative and reminder for the chosen foreign policy which should be more humane by respecting human dignity, which must be upheld and cannot be disregarded.